APPLICATION TO DIAGNOSE INTERNET ADDICTION ON STUDENTS/ HIGHER EDUCATION BASED ON WEB-BASED USING FORWARD CHAINING METHOD - Humdiana, Humdiana; Edwin, Edwin (International Journal of Social Science, 2022)
The rapid development of technology makes everything easier. As time passes, technology is growing and human needs can be easily fulfilled. The problem in technological development that is going faster every day is that the development can not be stopped, but the standard of human need for technology will be higher. Researchers write the meaning of application and internet addiction which is the topic of this scientific work. The researcher is using the Forward Chaining method in the process of making this application and using the Waterfall model as a system development method. Researchers also include the understanding of the internet, and the object that researcher researched, which is college student. Researcher gather information by questionnaires and literature study, collecting information such as student data from various colleges and reviewing for books, journals and websites for reference to this research. This website is created to determine the internet addiction of college students in general so college students and parents can find out the impact and find solutions for those who have Internet addiction. Through the research process and the website development that has been done, the researcher concludes that the website that the researchers has created can be useful for students to determine the level of internet addiction owned by the student